PTH-090 A new model of consultation to facilitate a patient centred approach in the IBD clinic. Issue 2 (June 2019) - Tattersall, Suzanne; Ahmed, Shahd; Fairhurst, Francesca; Hall, Veronica; Lipscomb, George; Ndlovu, Zandile; Singh, Salil
Abstract : Introduction: The consultation is a pivotal event in the clinician/patient relationship, defined as the act of seeking assistance from a physician in order to benefit their patient. However, studies support that in only 23% of consultations was the patient allowed to complete their opening statement of concern, and in 69% of cases the physician interrupted the patient's statement to re-direct the enquiry to the physician's agenda. This IBD service recognised the paradigm in its approach to patient consultation. An innovative patient centred agenda sheet was developed In order to redesign the consultation model to allow patients the opportunity to put forward their concerns to be addressed during the consultation. Methods: A patient agenda sheet was developed. Page one included; an objective, rapid assessment tool, utilising the Bristol stool chart alongside an amalgamation of the Harvey Bradshaw index and Simple Clinical Colitis Activity Index. This allows the clinician to quickly establish disease activity and severity. Page two is a free text section which includes suggestions for discussion points during the consultation which prompts the patient to address their concerns. Patient agenda sheets were distributed when patients arrived in clinic to be completed in the waiting room. The sheets were used by the clinicians as a prompt during the consultation. An audit of 100 clinic letters and patient agenda sheets was undertaken to establish emerging themes. The clinician perspective regarding the use of the patient agenda sheet was also analysed. Results: Uptake was positive with a 94% completion rate. There were six main themes identified included; medication issues, managing flare ups, fertility, travel, surveillance colonoscopy and general check-ups. The agenda sheet reduced clinician time spent establishing disease activity and focused the consultation on addressing the patient's agenda. Conclusion: We successfully changed the consultation model from a physician's agenda to a patient centred approach. As well as empowering patients to discuss the issues that concern them, the patient agenda sheet has allowed clinicians to identify topics within the consultation which may not have previously addressed such as pregnancy and fertility. Furthermore it has facilitated rapid signposting to appropriate clinics such as Guided Self- management.